(untitled) (International Journal of Engineering and Computer Science, 2017)
The chip design in the 21st century has undergone various changes due to the increased customer demands and this lead to design complexity in systems-on-chip (SoC), network-on-chip (NoC), application-specific integrated circuit (ASIC), and field-programmable gate array (FPGA) designs. This creates a situation to develop an advanced system to resolve the complexity issue in meantime. The verification step consumes the major portion of the VDHL time and transaction-level modeling (TLM) and Bus Functional modeling (BFM) are used in order to reduce this effort. Transaction-level modeling (TLM) is a technique used to describe the system by using the standard function calls which defines all the transactions which are required to verify the functionality of the system at the architecture level. The usage of the transaction based techniques are designed for the software analysis and for the first time, in this research work it is used for the physical hardware design and its analysis based on the AMBA ace-lite architecture. In past AMBA AXI4 Bus Interconnects is used for the hardware system design but it fails to meet the practical design requirements and the proposed AMBA ace-lite architecture has yielded the desired results with low complexity. With the proposed AMBA ace-lite architectural design for hardware system design, several SoC/NoC subsystems can easily be interconnected in basically the same manner as how transaction-based simulation models are being written. The proposed methodology is useful for the hardware design engineers to deal with the complexity simplification issues by bringing the benefits of transaction-based verification (TBV) to it approach.